The relationship between total quality management and firm performance at Majlis Agama Islam dan Adat Melayu Perak (MAIPk), Ipoh, Perak / Norsiha Abdul Hanid - Abdul Hanid, Norsiha (2017)
This study to investigate the relationship between Total Quality Management between Firm Performance at Majlis Agama Islam Dan Adat Melayu Perak (MAIPk), Ipoh, Perak. Hence, for this research, the researcher decided to distribute the questionnaires to only 103 of employee Majlis Agama Islam Dan Adat Melayu Perak (MAIPk), Ipoh, Perak. The objectives of this study were to identify the most contributing factor of Total Quality Management towards Firm Performance at Majlis Agama Islam Dan Adat Melayu Perak (MAIPk), Ipoh, Perak and to examine the relationship between Total Quality Management and Firm Performance at Majlis Agama Islam Dan Adat Melayu Perak (MAIPk), Ipoh, Perak. Moreover, this study provided a lot of advantage to the researcher and the people in the organization because it created more understanding on the relationship between Total Quality Management and Firm Performance. There were three elements in Total Quality Management that been studied which were training, leadership and customers focus. Finding in this study concludes the most contributing factor of total quality management towards firm performance at Majlis Agama Islam Dan Adat Melayu Perak (MAIPk), Ipoh, Perak was training with the highest mean 4.1883. While, leadership with mean .41534 and customer focus with mean 4.1534. While, based on the findings in correlation analysis, there is strong, positive relationship between Total Quality Management and firm performance among employees Majlis Agama Islam Dan Adat Melayu Perak (MAIPk), Ipoh, Perak which was statistically significant with value (r=.639, p<.01).